The Implementation of Corporate Social Responsibility of PT Bakrie Sumatera Plantations on the Welfare of the Bunut Subdistrict Community Based on Government Regulation No. 47 of 2012 - Sri Devi; Emiel Salim Siregar (DE'RECHTSSTAAT, 2026)
Corporate Social Responsibility is governed by Government Regulation No. 47 of 2012, which pertains to the social and environmental responsibilities of Limited Liability Companies. PT. Bakrie Sumatera Plantations persists in executing its Corporate Social Responsibility program to the present day. This study seeks to assess the efficacy and efficiency of the Corporate Social Responsibility program established for the benefit of the Bunut Village community. This study employs a form of empirical legal research known as sociological legal research or field research. The research findings indicate that PT. Bakrie Sumatera Plantations has executed multiple Corporate Social Responsibility initiatives throughout Education, Religion, Economy, Youth, Infrastructure, and Disaster Response sectors. The established programs have been operating efficiently in compliance with Government Regulation No. 47 of 2012 and have positively influenced community welfare. Consequently, this has led the people to rely on the Company, diminishing their independence. This is due to the Company's failure to communicate and promote the Corporate Social Responsibility program to the local Community. Consequently, the community lacks comprehension of the concept, execution, and aims of Corporate Social Responsibility.